IMPROVING STUDENTS' UNDERSTANDING OF LIGHTS AND OPTICS AND UNDERSTANDING ABOUT NATURE OF SCIENCE (NOS) THROUGH INQUIRY BASED LABORATORY ACTIVITY - Wardani, Tiara Budi (2017)
The aim of this study was to determine the effect of inquiry-based laboratory activities on the understanding of light and optical topics and understanding of the nature of students' sciences. The method used in this research is quasi experiment. Sampling technique using cluster random sampling, samples taken from grade 8 in one of junior high school in Bandung regency. The sample numbered 45 students, consisting of the experimental class (n = 24 students) and and the control class (n=21 students). The experimental class is taught by inquiry-based laboratory activities, while the control class is taught by non-inquiry laboratory activities. The result of this research is, N-Gain conceptual understanding on experiment class shows the number of 0.76 which is categorized as high improvement, whereas in control class 0,58 is categorized as medium improvement. Improved conceptual understanding of students can be seen with independent sample t test with significant 0.004 which means there is a significant difference between the experimental and control classes. The students' understanding of the nature of science shows that the experimental class got NGain of 0.60. While the controls got N-Gain of 0.44, and both classes proven to have statistically significant different improvement.----------Tujuan dari penelitian ini adalah untuk mengetahui pengaruh kegiatan laboratorium berbasis inkuiri terhadap pemahaman pada topik cahaya dan optik dan pemahaman tentang hakikat sains siswa. Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen. Teknik pengambilan sampel menggunakan cluster random sampling, sampel diambil dari kelas 8 di salah satu SMP di Kabupaten Bandung. Sampel berjumlah 45 siswa, terdiri dari kelas eksperimen (n=24 siswa) dan dan kelas kontrol (n = 21 siswa). Kelas eksperimen diajar dengan kegiatan laboratorium berbasis inkuiri, sedangkan kelas kontrol diajar dengan kegiatan laboratorium non inkuiri. Hasil penelitian ini adalah, N-Gain pemahaman konseptual pada kelas eksperimen menunjukkan jumlah 0,76 yang dikategorikan sebagai peningkatan tinggi, sedangkan pada kelas kontrol 0,58 dikategorikan sebagai peningkatan sedang. Peningkatan pemahaman konseptual siswa dapat dilihat dengan uji t sampel independen dengan signifikan 0,004 yang berarti ada perbedaan yang signifikan antara kelas eksperimen dan kontrol. Pemahaman siswa tentang hakikat sains menunjukkan bahwa kelas eksperimen mendapat N-Gain sebesar 0,60. Sedangkan kontrol mendapat N-Gain sebesar 0,44, dan kedua kelas terbukti secara statistik memiliki peningkatan yang signifikan berbeda.